The Impact of Entrepreneurship Orientation on Entrepreneurs Compensation in Nigeria - Kayode, ADISA, Matthew; Olarewaju, ADEOYE, Abayomi; Idowu, OKUNBANJO, Olajide (International Journal of Economics, Business and Management Studies, 2016)
The objective of this study is to investigate the impact of entrepreneurship orientation on entrepreneurs compensation. A total of 270 questionnaires were administered but 255 questionnaires were found usable and data was analysed through regression and Pearson correlation. Three hypotheses were tested and the result shows that there is no positive association between risk-taking and financial compensation of an entrepreneur but a weak association exists between innovativeness and competitive aggressiveness and non-financial compensation of an entrepreneur. The study recommended that entrepreneurship education should be introduced in Nigeria’s educational system and trainings, seminars and conferences should also be organized for prospective entrepreneurs.